SOME OBSERVATIONS ON THE EARLY BIOLOGICAL STAGES OF EUSARCOCORIS CA PITA TUS DISTANT, A PEST OF HOLY TULSI, OCIMUM SANCTUM L. - JAIN, SHILPI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
E. capitatus (Heteroptera : Pentatomidae) is a pest of holy Tulsi, Ocimum sanctum L. which in turn is an ¡mportant medicinal plant grown in most of the pious Hindu families as well as in kitchen gardens. Damage is caused by desapping habit of the bug population to the seeds, inflorescence and leaves. The result of laboratory rearing revealed that a copulation period of 2 to 19 hrs with anaverage of 7.5 hrs is required and prior to it the bug needs a pre-copulation period of 4 to 13 days average being 7.8 days. Oviposition begins after 4 to 42 hrs of copulation average being 20.1 hrs. Oviposting female selects a suitable oviposting site with the help of rostral tip and antennal sensillae. Aftei ng a suitable site, it leans forward, levels her abdomen and its inter- valvular space is opened through which egg starts its journey out. As soon as candal end of egg is exposed a sticky substance is exuded by accessory gland. As soon as egg come out, it is glued to the substratum. 5 to 12 minutes are required for laying an egg and 30 to 480 minutes for laying an egg batch. Time between succesšive egg laying extends from 10 to 65 minutes. Egg are deposited on the inflorescence in between the flowers and seeds. Eggs are laid singly and rarely two or three eggs may be laid side by side. However, no egg was seen laid on leaves. Láid egg measures on an average 0.4 1mm in length and 0.29mm in width. Its chorion is rough, shape is cylindrical. On its cephalic end there is a ring of 10 to 16 (average 12) micropylar processes. Newly laid egg is milky white and its colour changes gradually as the development of embryo inside it proceeds. It turns light pinkish, light reddish, and at the last dark red before hatching. An incubation period of 3 to 5 days (average 4 days) is required prior to hatching. During hatching opercular part having micropylar rings ruptures which may separates off completely or remain attached at one side. Through opened egg, first instar nymph comes out. Hatching period varies from 3 to 7 minutes with an average of 4.5 minutes. After hatching, first instar nymph dries its appendages on exposure to air. Its colour was reddish brown, It requires 3 to 5 days (average 3.7days) nymphal period or growth period after which it moults into second instar nymph. It measures 0.88 mm to 1.00mm. in length (average 0.93mm ) and 0.6mm to 0.72mm in width (average 0.67mm).